METHODOLOGY OF ESTIMATION OF EFFICIENCY OF FUNCTIONING RECOVERY SYSTEM OF MILITARY SPECIAL VEHICLES - Анатолій Григорович Салій; Василь Володимирович Поліщук; Валентин Петрович Диптан; Василь Іванович Іванов (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The article highlights the algorithm of selection the indicators and benchmarks functioning of the restoration automotive system and special equipment of the military, and through the use of those indicators and criteria offered an improved method of evaluating the effectiveness functioning of the system in conditions of performance tasks.